Dominant Components of Technical Aspects in Identification of Football Athlete Talent Using AHP - Hafidz Nashrul Ghani; Rusdiana, Agus; Subarjah, Herman; Syahid, Angga M; Kurniawan, Tian (Universitas PGRI Palembang, 2024)
The aim of this research is to assess which technical aspects are dominant in identifying football athletes using the Analytic Hierarchy Process (AHP). This research uses a combination method. Mixed Methods Research (MMR) is a research approach that combines elements of qualitative and quantitative approaches in one Study. The sample used in this research consisted of 10 coaches in the sport of soccer, who had a national coaching license with more than 5 years of coaching experience in the sport of soccer. Data collection was carried out using a questionnaire distributed online via Google Form. From the results of this analysis, it is proven that passing has a very important role compared to other criteria. The order of priority scores obtained from this analysis is as follows: Passing = 0.420; Control = 0.253; Dribbling = 0.144; Shooting = 0.126; and Post = 0.057. The conclusion in this study is that passing has a higher percentage in the assessment. This shows that passing is the main factor in detecting the talent of soccer athletes.